2010
DOI: 10.1002/ar.21294
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Passive Stretch and NF‐κB Inhibitors on the Morphology of Dystrophic Muscle Fibers

Abstract: The triangularis sterni (TS) is an expiratory muscle that is passively stretched during inspiration. The magnitude of passive stretch depends upon the location of individual fibers within the TS muscle, with fibers located more caudally being stretched $ 5% to 10% more than fibers in the cephalad region. In the mdx mouse model for muscular dystrophy, the TS exhibits severe pathological alterations that are ameliorated by treatment with inhibitors of the NF-jB pathway. The purpose of this study was to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(47 citation statements)
references
References 27 publications
10
37
0
Order By: Relevance
“…The mean RP of untreated fibers in the caudal region of the severely dystrophic mdx TS muscle [20] at 7 to 9 months of age (−54.8 ± 0.9 mV, N = 208 fibers, 19 muscles) was 4.2 mV less negative (p<0.01, Mann-Whitney Rank Sum Test) than that observed in nondystrophic TS muscles (−59.0 ± 0.7 mV, N= 128 fibers, 12 muscles). Fibers from a cohort of nondystrophic mice (7 to 9 month) were depolarized by 14.7 mV (from −61.1 to −46.4 mV; N= 80 fibers, 8 muscles) following a 30 minute exposure to 1 mM ouabain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean RP of untreated fibers in the caudal region of the severely dystrophic mdx TS muscle [20] at 7 to 9 months of age (−54.8 ± 0.9 mV, N = 208 fibers, 19 muscles) was 4.2 mV less negative (p<0.01, Mann-Whitney Rank Sum Test) than that observed in nondystrophic TS muscles (−59.0 ± 0.7 mV, N= 128 fibers, 12 muscles). Fibers from a cohort of nondystrophic mice (7 to 9 month) were depolarized by 14.7 mV (from −61.1 to −46.4 mV; N= 80 fibers, 8 muscles) following a 30 minute exposure to 1 mM ouabain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The left TS muscle was removed as previously described [6, 12, 20] and placed in a muscle chamber containing mouse Ringer solution (in mM: 125 NaCl, 5 KCl, 2 CaCl 2 , 24 NaHCO 3 , 1 NaH 2 PO 4 , 11 glucose, pH 7.35; room temperature). The solution was continually re-circulated and bubbled with 95% O 2 /5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4-PBA-treated diabetic group (n = 12), treated with 100 mg/kg/d 4-PBA (Santa Cruz Biotechnology, CA, USA) in vehicle. 23,24 All mice were treated for 12 weeks.…”
Section: Materials and Methods Animals And Groupingmentioning
confidence: 99%
“…Several studies have indicated that dystrophic human and murine ( mdx ) muscle exhibits substantial increases in NF‐κB signaling and that inhibition of the NF‐κB pathway in vivo improves muscle structure and function in the mdx model for Duchenne muscular dystrophy . Ursodeoxycholic acid (UDCA) is composed of a substituted 17 carbon steroid backbone and is used clinically to treat hepatobiliary disorders .…”
mentioning
confidence: 99%